Sensors in highway and civil engineering proceedings of the conference organized by the Institution of Civil Engineers, London, 5 February 1981. (Thomas Telford, 1981)
The focus of these papers ranges from laser control of construction equipment to measurement of road surface shape using a laser sensor. They also provide traffic data from aerial photography using semi-automatic methods.